Effects of Alzheimer and Lewy Body Disease Pathologies on Brain Metabolism. Issue 6 (8th April 2022) - Lee, Young‐gun; Jeon, Seun; Park, Mincheol; Kang, Sung Woo; Yoon, So Hoon; Baik, Kyoungwon; Lee, Phil Hyu; Sohn, Young Ho; Ye, Byoung Seok
Abstract : Objective: This study aimed to determine the pattern of 18 F‐fluorodeoxyglucose positron emission tomography (FDG‐PET) related to postmortem Lewy body disease (LBD) pathology in clinical Alzheimer disease (AD). Methods: FDG‐PET scans were analyzed in 62 autopsy‐confirmed patients and 110 controls in the Alzheimer's Disease Neuroimaging Initiative. Based on neuropathologic evaluations on Braak stage for neurofibrillary tangle, Consortium to Establish a Registry for AD score for neuritic plaque, and Lewy‐related pathology, subjects were classified into AD(−)/LBD(−), AD(−)/LBD(+), AD(+)/LBD(−), and AD(+)/LBD(+) groups. The association between postmortem LBD and AD pathologies and antemortem brain metabolism was evaluated. Results: AD and LBD pathologies had significant interaction effects to decrease metabolism in the cerebellar vermis, bilateral caudate, putamen, basal frontal cortex, and anterior cingulate cortex in addition to the left side of the entorhinal cortex and amygdala, and significant interaction effects to increase metabolism in the bilateral parietal and occipital cortices. LBD pathology was associated with hypermetabolism in the cerebellar vermis, bilateral putamen, anterior cingulate cortex, and basal frontal cortex, corresponding to the Lewy body‐related hypermetabolic patterns. AD pathology was associated with hypometabolism in the bilateral hippocampus, entorhinal cortex, and posterior cingulate cortex regardless of LBD pathology, whereas LBD pathology was associated with hypermetabolism in the bilateral putamen and anterior cingulate cortex regardless of AD pathology. Interpretation: Postmortem LBD and AD pathologies had significant interaction effects on the antemortem brain metabolism in clinical AD patients. Specific metabolic patterns related to AD and LBD pathologies could be elucidated when simultaneously considering the two pathologies. ANN NEUROL 2022;91:853–863